FEATURES OF THE RAMAN SCATTERING IN QUASIPERIODIC NANOSTRUCTURES OF POROUS SILICON - Mamichev, D.; Mussabek, G.; Goryachev, V.; Golovan, L.; Taurbayev, Ye.; Timoshenko, V.Yu.; Taurbayev, T.I. (Recent Contributions to Physics, 2018)
The possibility of intensity enhancement of Raman scattering of near infrared light on the photon band gap edge in periodic multilayer structures produced from porous silicon consisting of porous silicon layers sequences with a high and low refractive index was shown theoretically and experimentally. The obtained results show perspectivity of use of these structures as a matrix for enhancement of Raman scattering efficiency.